2004
DOI: 10.1113/jphysiol.2004.061143
|View full text |Cite
|
Sign up to set email alerts
|

A glucocorticoid‐induced Na+ conductance in human airway epithelial cells identified by perforated patch recording

Abstract: The perforated patch recording technique was used to investigate the effects of dexamethasone (0.2 microm, 24-30 h), a synthetic glucocorticoid, on membrane conductance in the human airway epithelial cell line H441. Under zero current clamp conditions this hormone induced amiloride-sensitive depolarization of the membrane potential (V(m)). Lowering external Na(+) to 10 mm by replacing Na(+) with N-methyl-d-glucammonium (NMDG(+)) also hyperpolarized the dexamethasome-treated cells, whilst replacing Na(+) with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
56
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(73 citation statements)
references
References 44 publications
16
56
1
Order By: Relevance
“…14). Subsequently, lowering [Na ϩ ] o to 10 mM (NMDG ϩ substitution), in the continued presence of 10 M amiloride, caused further hyperpolarization to Ϫ68.1 Ϯ 2.4 mV (P Ͻ 0.05), which also accords with the earlier data (14), and analysis of I Na(Ϫ82 mV) (see METHODS) indicated that amiloride caused 92.8% Ϯ 1.2% inhibition (P Ͻ 0.005) of I Na under these conditions (Fig. 9B).…”
Section: Effects Of Insulinsupporting
confidence: 82%
See 4 more Smart Citations
“…14). Subsequently, lowering [Na ϩ ] o to 10 mM (NMDG ϩ substitution), in the continued presence of 10 M amiloride, caused further hyperpolarization to Ϫ68.1 Ϯ 2.4 mV (P Ͻ 0.05), which also accords with the earlier data (14), and analysis of I Na(Ϫ82 mV) (see METHODS) indicated that amiloride caused 92.8% Ϯ 1.2% inhibition (P Ͻ 0.005) of I Na under these conditions (Fig. 9B).…”
Section: Effects Of Insulinsupporting
confidence: 82%
“…Analysis of the present data showed that V m was normally Ϫ3.7 Ϯ 3.8 mV, although, as reported previously (14), there was variability between the values of V m measured in different cells (range: Ϫ20.7 to 20.2 mV), and analysis of the data from all experiments included in the present study in which membrane currents were recorded from such groups of cells showed that the mean value of V m was approximately Ϫ20 mV. This is very similar to the previously reported value (14). Under these conditions, amiloride (10 M, 30 -45 s) hyperpolarized V m to Ϫ56.7 Ϯ 1.5 mV (P Ͻ 0.005) and reduced the inward currents flowing at negative values of V Hold .…”
Section: Effects Of Insulinsupporting
confidence: 77%
See 3 more Smart Citations